Financial Management Practices and Sustainability of Non Governmental Organisations Projects in Juba, South Sudan - Wandera, Tom Victor; Sang, Dr. Paul (International Journal of Finance, 2017)
Purpose: The purpose of this study was to investigate the effect of financial management challenges on financial sustainability of Non-Governmental Organizations in south Sudan. Methodology: The study used descriptive research design. The target population of the study was all the 112 NGO in South Sudan at July 31st 2015. A census of all the 112 key financial manager personnel was taken since the population is small. Primary data was collected through the administration of the questionnaires. This study generated both qualitative and quantitative data. Data was analyzed mainly by use of descriptive and inferential statistics that is, graphical and numerical methods, measures of central tendencies as well as measures of variability. The particular inferential statistics were regression and correlation analysis. Multiple regression equation was used to determine the strength and directions of the association between the variables with the results. Results: The study findings indicated that there is a significant and positive relationship between budget control and the financial sustainability of NGOs in South Sudan. The results also indicated that there is a significant and positive relationship between financial reporting and the financial sustainability of NGOs in South Sudan. Also, results found out that there is a significant and positive relationship between income source diversification and the financial sustainability of NGOs in South Sudan. Further, the results indicated that there is a significant and positive relationship between donor relationship management and the financial sustainability of NGOs in South Sudan. Unique contribution to theory, practice and policy: The study recommended that budget control activities such as financial resources, competent human resource, and participation of both staff and other stakeholders in the budgeting process, proper planning, evaluation, monitoring and control of the budget process and staff motivation should be fully adopted by NGOs in order to sustain their financials. The study also recommended that income source diversification activities such as charitable donations from individuals and corporations, grants, fees, commission, contracts for service, and sales of goods and should be adopted in order to enhance the financial sustainability of NGOs.